Fungicidal protection of sunflower against the main leaf diseases - Retman, S.; Bazykina , N. (Quarantine and plant protection, 2019)
Goal. To determine the technical efficiency of the novel fungicides against the diseases of leaves sunflower and to establish the optimal terms of fungicidal treatments for the zone of the Right Bank Forest-steppe of Ukraine. Research methods. Field and laboratory. The research was conducted during 2014—2017 in the Right-bank Forest-steppe of Ukraine (Khmelnytsky region) on the Canyon hybrid investigated the effect of fungicides Pictor, SC (0.5 l / ha), Retengo, EC (0.75 l / ha), Amistar Extra 280 SC, SC (0.75 l / ha) was investigated. The treatments were carried out in two terms: once — on 32 and 53 stages on the BBCH scale and twice — at the same terms. The records were performed before application and on the 15th and 30th day after it. The observations were conducted according to generally accepted methods; the incidence and severity of diseases, technical efficiency were determined. Results. It was determined that crops annually struck affected leaf disease Alternaria and Septoria. The highest development was recorded for alternaria leaf spot — 22.5%. For both single and double spraying, the highest level of protection against septoria leaf blotch was observed for the application of Amistar Extra 280 SC, SC (0.75 l / ha), while Pictor, SC (0.5 l / ha) was more efficient against alternaria leaf spot. Conclusions. Te two-fold application of fungicides is more effective, it reduces the development of leaf diseases by 78—96% and preserves the crop within 0,41—0,53 t / ha. Among the studied fungicides, Pictor, EC and Amistar Extra 280 SC, SC showed superior efficacy for all investigated terms.